2014
DOI: 10.1134/s1063773714050028
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical rates of pulsation period change in the Galactic Cepheids

Abstract: Theoretical estimates of the rates of radial pulsation period change in Galactic Cepheids with initial masses 5.5M_\odot <= Mzams <= 13M_\odot, chemical composition X=0.7, Z=0.02 and periods 1.5 day <= P <= 100 day are obtained from consistent stellar evolution and nonlinear stellar pulsation computations. Pulsational instability was investigated for three crossings of the instability strip by the evolutionary track in the HR diagram. The first crossing occurs at the post-main sequence helium core gravitationa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
12
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 19 publications
(19 reference statements)
7
12
1
Order By: Relevance
“…Turner et al (2007) propose a much lower value of 0.082 ± 0.012 s/yr, which is closer to our own value of 0.124 ± 0.036 s/yr. This period change is that expected for a Cepheid crossing the instability strip for the third time (Fadeyev 2014). Turner et al (2007) observed a sinusoidal trend in the O-C diagram, which is interpreted as a light-time effect produced by a long period orbit companion.…”
Section: Rt Aursupporting
confidence: 62%
See 4 more Smart Citations
“…Turner et al (2007) propose a much lower value of 0.082 ± 0.012 s/yr, which is closer to our own value of 0.124 ± 0.036 s/yr. This period change is that expected for a Cepheid crossing the instability strip for the third time (Fadeyev 2014). Turner et al (2007) observed a sinusoidal trend in the O-C diagram, which is interpreted as a light-time effect produced by a long period orbit companion.…”
Section: Rt Aursupporting
confidence: 62%
“…Meyer (2006) mentioned that the change rate is in the interval of −0.25 ± 0.13 s/yr with a probability of 99%, while Turner (1998) suggests a similar value of −0.24 s/yr. We find a disagreeing value of 0.060 ± 0.035 s/yr, which would place in T Vul rather in the third crossing of the instability strip (Fadeyev 2014). Whether or not we include the interferometric data in the SPIPS fit leads to consistent results, although the amplitude of the diameter variation tends to be slightly underestimated.…”
Section: T Vulcontrasting
confidence: 51%
See 3 more Smart Citations